Ablation-resistant coating as well as preparation method and application thereof
By synthesizing P-Si with Si-O-Si crosslinked structure and mixing it with other materials in proportion, a resistant ablation coating was prepared, which solved the problem of degradation of traditional coatings at high temperatures and achieved improvements in high ablation temperature and wear resistance.
Patent Information
- Application Number
- CN202510276950.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-10
AI Technical Summary
After hundreds of ablation-resistant injection frictions, the strength and durability of the coating will decrease, making it difficult to meet the requirements of high ablation temperature and wear resistance.
By synthesizing P-Si with Si-O-Si crosslinked structure and mixing it with expandable graphite, silicon carbide, zirconium carbide, ammonium polyphosphate raw material solid powder and ceramic fibers in proportion, ablation-resistant coating is prepared and applied to metal or ceramic tube walls.
This ablation-resistant coating significantly improves the ablation temperature and wear coefficient of the pipe wall, can maintain stability at high temperatures, reduce mass loss rate, and extend the service life of the coating.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to coating technology, and in particular to an ablation-resistant coating and a preparation method and application thereof. Background Art
[0002] The fast-feeding fixture with good ablation-resistant coating is a key component of the ablation test equipment, and plays a vital role in achieving fast-feeding and protecting the ablation test equipment. Traditional ablation-resistant coatings often cause the strength and function of the coating to decrease after hundreds of ablation-resistant feeding frictions. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide an ablation-resistant coating with high ablation-resistant temperature and wear-resistant coefficient and the preparation and application thereof.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: by synthesizing P-Si with a Si-O-Si cross-linked structure, processing expandable graphite, silicon carbide, zirconium carbide, and ammonium polyphosphate raw material solid powders mixed in proportion, and mixing the two with ceramic fibers in proportion at a temperature of 140°C to 150°C to prepare an ablation-resistant coating, which is applied to the metal or ceramic pipe wall, and can effectively improve the ablation resistance temperature and wear resistance coefficient of the pipe wall, thereby achieving the purpose of the present invention.
[0005] The present invention relates to a method for preparing an ablation-resistant coating, and the preparation steps are as follows: 1) Synthesis of P-Si with Si-O-Si cross-linked structure Tetramethoxysilane and γ-glycidyloxypropyltrimethoxysilane in a mass ratio of 1:(4-6) are added to tetrahydrofuran, wherein the material-liquid ratio is (50-70) g:200 mL; the temperature is raised to 80°C-100°C while stirring under nitrogen protection, and the stirring is stopped after the reaction is continued for 6h-10h; the polysilane filler P-Si with Si-O-Si crosslinking structure is obtained under nitrogen protection. The structural formula is as follows:
[0006] 2) Treatment of inorganic fillers The expandable graphite, silicon carbide, zirconium carbide and ammonium polyphosphate raw material solid powders in a mass ratio of (1-1.1):(1-1.1):(3-3.2):(0.5-0.7) are uniformly mixed and added to tetramethoxysilane, wherein the material-liquid ratio is (55-57) g:(200-250) mL, and the mixture is fully stirred at a temperature of 140° C. to 150° C., and then centrifuged. The treated lower layer product is fully stirred with γ-glycidyloxypropyltrimethoxysilane at a temperature of 130° C. to 140° C., wherein the material-liquid ratio is 100 g:(200-250) mL, and then centrifuged again. The lower layer product after centrifugation is ground to obtain a treated inorganic filler; 3) Preparation of ablation-resistant coating At a temperature of 140°C to 150°C, the treated inorganic filler and P-Si having a Si-O-Si cross-linked structure are mixed and stirred for at least 10 hours, and then ceramic fibers are added and the mixing and stirring is continued for at least 5 hours to obtain the ablation-resistant coating, wherein the mass ratio of the treated inorganic filler, P-Si having a Si-O-Si cross-linked structure and ceramic fibers is (2-20):(1-9):(2-20).
[0007] Preferably, in step 2) of treating the inorganic filler, the particle sizes of the expandable graphite, silicon carbide, zirconium carbide and ammonium polyphosphate are 10 μm to 100 μm, and the mass ratio is 1:1:3:(0.5-0.7).
[0008] Preferably, in step 2) treating the inorganic filler, the particle size of the treated inorganic filler is 10 μm to 100 μm.
[0009] Preferably, in step 2) treating the inorganic filler, the centrifugal treatment operation is performed for no less than 20 minutes.
[0010] Preferably, in step 3) preparing the ablation-resistant coating, the diameter of the ceramic fiber is 2 μm to 5 μm.
[0011] The present invention also relates to an ablation-resistant coating, which is mixed with treated inorganic fillers, P-Si with a Si-O-Si cross-linked structure, and ceramic fibers in a mass ratio of (2-20):(1-9):(2-20).
[0012] The present invention also relates to the application of the ablation-resistant coating, which is applied to a metal or ceramic pipe wall and then left to stand and solidify to obtain the ablation-resistant coating.
[0013] Preferably, the tube wall is the inner wall of the ablation test sample conveying tube.
[0014] Preferably, the coating thickness of the ablation-resistant coating on the pipe wall is 2 mm to 6 mm.
[0015] The invention relates to a method for preparing an ablation-resistant coating, wherein P-Si with a Si-O-Si cross-linked structure is synthesized, and a proportion of expandable graphite, silicon carbide, zirconium carbide, and ammonium polyphosphate raw material solid powders are processed, and the two are mixed with ceramic fibers in proportion at a temperature of 140°C to 150°C. The P-Si with a Si-O-Si cross-linked structure is modified by a proportion of expandable graphite, silicon carbide, zirconium carbide, and ammonium polyphosphate composites, and the heat extension in the long chain direction is retained in the long chain structure γ-glycidyloxypropyltrimethoxysilane and the branched structure tetramethoxysilane, and the steric hindrance effect of the branched structure is also obtained; by optimizing the ratio of the P-Si with a Si-O-Si cross-linked structure and the treated inorganic filler, the effects of the two are balanced, and the coating stability under high temperature is improved. In addition, the adhesion of the treated inorganic filler is enhanced by the activation of the silane polymer with a similar structure of Si-O-Si cross-linked structure, and the ablation temperature and wear resistance coefficient of the ablation-resistant coating are improved. DETAILED DESCRIPTION The specific implementation methods of the present invention are used to provide necessary disclosure for those skilled in the art to fully understand the present invention, and are intended to effectively support the claims of the present invention. At the same time, this section will involve the interpretation or definition of the features and terms of the technical solution of the present invention. Those skilled in the art should understand the scope of the claims of the present invention in conjunction with the explanation of the specific features and terms in the specification, and should not arbitrarily distort the true connotations represented by the features and terms of the present invention.
[0016] It must be understood that in any work involving the definition of the scope of the claims of the present invention, the specific embodiments provided by the present invention can be used to fully support the appropriate summaries of equivalent or superior solutions summarized therefrom, and the scope of the claims should never be understood as not exceeding the examples themselves. It must also be understood that with the development of technology and the emergence of new scenarios, the technical solutions provided by the embodiments of the present application will also be applicable to similar technical problems within the scope of those skilled in the art without any creative work, and the scope of protection of the present invention should not be limited to the examples recorded in the specific implementation methods of the present invention.
[0017] Example 1 The ablation-resistant coating of this embodiment is prepared by mixing treated inorganic fillers, P-Si having a Si-O-Si cross-linked structure, and ceramic fibers in a mass ratio of 2:1:2, and the preparation method is as follows: 1 Synthesis of P-Si with Si-O-Si cross-linked structure 10g of tetramethoxysilane and 60g of γ-glycidyloxypropyltrimethoxysilane were added to 200mL of tetrahydrofuran, stirred at 400 rpm under nitrogen protection gas and heated to 100°C at the same time, and the stirring was stopped after the reaction for 10h; then, the mixture was cooled to room temperature under nitrogen protection gas to obtain a polysilane filler P-Si with a Si-O-Si cross-linked structure. The synthetic chemical formula of P-Si is as follows:
[0018] 2 Treatment of inorganic fillers 57g of solid powder of ammonium polyphosphate with a particle size of 10μm was mixed with expandable graphite with a mass ratio of 1:1:3:0.7, silicon carbide with a particle size of 20μm, zirconium carbide with a particle size of 15μm, and ammonium polyphosphate with a particle size of 10μm. After stirring for 1h to make them evenly mixed, they were added to 200mL of tetramethoxysilane, stirred at 150°C for 5h, and then centrifuged for 20min. 100g of the lower layer product after centrifugation was taken and stirred with 200mL of γ-glycidyloxypropyltrimethoxysilane at 140°C for 10h, and then centrifuged for 20min. The lower layer product after centrifugation was ground to 10μm to obtain a treated inorganic filler.
[0019] 3 Preparation of ablation-resistant coating At 150°C, 100g of the treated inorganic filler was stirred with 50g of P-Si for 10h, and then 100g of ceramic fiber with a diameter of 2μm was added and stirred for 5h to obtain an ablation-resistant coating, which was then sealed and stored in the dark.
[0020] The ablation-resistant coating prepared in this embodiment was coated with a thickness of 2 mm according to GB / T 17657-2022, and then subjected to a wear resistance test. The test results were as follows: 1. Ablation resistance temperature 1850℃; 2. Wear resistance at high temperature of 1400℃: wear value is 1g / 100r; 3. The mass loss rate after 500 times of rapid sampling at 1500℃ is less than 0.1%.
[0021] Example 2 The ablation-resistant coating of this embodiment is prepared by mixing treated inorganic fillers, P-Si having a Si-O-Si cross-linked structure, and ceramic fibers in a mass ratio of 5:2:5, and the preparation method is as follows: 1 Synthesis of P-Si with Si-O-Si cross-linked structure 10 g of tetramethoxysilane and 53 g of γ-glycidyloxypropyltrimethoxysilane were added to 200 mL of tetrahydrofuran, and the mixture was stirred at a speed of 400 rpm under nitrogen protection gas and heated to 87° C. The stirring was stopped after the reaction was continued for 7 hours; then, the mixture was cooled to room temperature under nitrogen protection gas to obtain a polysilane filler P-Si.
[0022] 2 Treatment of inorganic fillers 56g of solid powder of ammonium polyphosphate with a particle size of 100μm, 80μm silicon carbide, 100μm zirconium carbide and 90μm in mass ratio of 1:1:3:0.6 were mixed, stirred for 2h to make them evenly mixed, added to 250mL tetramethoxysilane, stirred for 7h at 140°C, and then centrifuged for 30min. 100g of the lower layer product after centrifugation was stirred for 12h with 250mL of γ-glycidyloxypropyltrimethoxysilane at 130°C, and then centrifuged for 30min. The lower layer product after centrifugation was ground to 100μm to obtain a treated inorganic filler.
[0023] 3 Preparation of ablation-resistant coating At 140°C, 100g of inorganic filler was stirred with 40g of P-Si for 12h, and then 100g of ceramic fiber with a diameter of 5μm was added and stirred for 6h to obtain ablation-resistant coating slurry, which was sealed and stored in the dark.
[0024] The ablation-resistant coating prepared in this embodiment was coated with a thickness of 2 mm according to GB / T 17657-2022, and then subjected to a wear resistance test. The test results were as follows: 1. Ablation resistance temperature 1700℃; 2. Wear resistance at high temperature of 1400℃: wear value is 1.5g / 100r; 3. The mass loss rate after 500 times of rapid sampling at 1500℃ is less than 0.1%.
[0025] Example 3 The ablation-resistant coating of this embodiment is prepared by mixing treated inorganic fillers, P-Si having a Si-O-Si cross-linked structure, and ceramic fibers in a mass ratio of 20:9:20, and the preparation method is as follows: 1Synthesis of P-Si with Si-O-Si cross-linking structure: 10 g of tetramethoxysilane and 40 g of γ-glycidyloxypropyltrimethoxysilane were added to 200 mL of tetrahydrofuran, stirred at a speed of 400 rpm under nitrogen protection gas and heated to 80° C. After reacting for 6 hours, stirring was stopped; then, the mixture was cooled to room temperature under nitrogen protection gas to obtain liquid polysilane filler P-Si.
[0026] 2. Treatment of inorganic fillers 55g of expandable graphite with a particle size of 50μm, silicon carbide with a particle size of 60μm, zirconium carbide with a particle size of 55μm and ammonium polyphosphate powder with a particle size of 70μm in a mass ratio of 1:1:3:0.5 were mixed, stirred for 1.5h to make them evenly mixed, added to 200mL of tetramethoxysilane, stirred at 150°C for 6h, and then centrifuged for 30min. 100g of the lower layer product after centrifugation was taken and stirred with 200mL of γ-glycidyloxypropyltrimethoxysilane at 140°C for 10h, and then centrifuged for 30min. The lower layer product after centrifugation was ground to 50μm to obtain a treated inorganic filler.
[0027] 3 Preparation of ablation-resistant coating At 150°C, 100g of inorganic filler was stirred with 45g of P-Si for 12h, and then 100g of ceramic fiber was added and stirred for 5h to obtain ablation-resistant coating slurry, which was then sealed and stored in the dark.
[0028] The ablation-resistant coating prepared in this embodiment was coated with a thickness of 2 mm according to GB / T 17657-2022, and then subjected to a wear resistance test. The test results were as follows: 1. Ablation resistance temperature 1670℃; 2. Wear resistance at high temperature of 1400℃: wear value is 1.6g / 100r; 3. The mass loss rate after 500 times of rapid sampling at 1500℃ is less than 0.1%.
[0029] Comparative Example 1 The difference from Example 3 is that: The ablation-resistant coating is mixed with treated inorganic filler and ceramic fiber in a mass ratio of 11:20, and the preparation method is as follows: 55 g of expandable graphite, silicon carbide, zirconium carbide and ammonium polyphosphate powder in a mass ratio of 1:1:3:0.5 were mixed evenly, then added into 200 mL of tetramethoxysilane, stirred at 150°C for 6 h, and then centrifuged for 30 min. 100 g of the lower layer product after centrifugation was taken and stirred with 200 mL of γ-glycidyloxypropyltrimethoxysilane at 140°C for 10 h, and then centrifuged for 30 min. 100 g of the lower layer product after centrifugation was taken and ground to 10 μm to obtain a treated inorganic filler; then 100 g of ceramic fiber was added and stirred for 5 h to obtain a slurry for sealed dark light storage.
[0030] The ablation-resistant coating prepared in this embodiment was coated with a thickness of 2 mm according to GB / T 17657-2022, and then subjected to a wear resistance test. The test results were as follows: 1. Ablation resistance temperature 740℃; 2. Wear resistance at high temperature of 1400℃: wear value: 2.1g / 100r; 3. The mass loss rate after 500 rapid sample loadings at 1500℃ is less than 0.27%.
[0031] Comparative Example 2 The difference from Example 2 is that: The ablation-resistant coating is prepared by mixing P-Si having a Si-O-Si cross-linked structure and an untreated inorganic filler in a mass ratio of 5:2. The preparation method is as follows: 1 Synthesis of P-Si with Si-O-Si cross-linked structure 10 g of tetramethoxysilane and 53 g of γ-glycidyloxypropyltrimethoxysilane were added to 200 mL of tetrahydrofuran, and stirring was started under nitrogen protection gas while heating to 87° C. After reacting for 7 hours, stirring was stopped at a stirring speed of 400 rpm, and the mixture was continued to be cooled to room temperature of 25° C. under nitrogen protection gas to obtain a polysilane P-Si having a Si-O-Si cross-linked structure.
[0032] 2 Preparation of ablation-resistant coating 100 g of expandable graphite, silicon carbide, zirconium carbide and ammonium polyphosphate powder in a mass ratio of 1:1:3:0.6 were uniformly mixed, stirred with 40 g of P-Si at 140°C for 12 h, and then 100 g of ceramic fiber was added and stirred for another 6 h to obtain a slurry which was sealed and stored in the dark.
[0033] The ablation-resistant coating prepared in this embodiment was coated with a thickness of 2 mm according to GB / T 17657-2022, and then subjected to a wear resistance test. The test results were as follows: 1. Ablation resistance temperature 1170℃; 2. Wear resistance at high temperature of 1400℃: wear value is 1.8g / 100r; 3. The mass loss rate after 500 rapid sample loadings at 1500℃ is less than 0.13%.
[0034] Comparative Example 3 The difference from Example 2 is that: The ablation-resistant coating is mixed with treated inorganic filler and ceramic fiber in a mass ratio of 1:1, and the preparation method is as follows: 56 g of expandable graphite, silicon carbide, zirconium carbide and ammonium polyphosphate powder in a mass ratio of 1:1:3:0.6 were mixed evenly, then added into 250 mL of tetramethoxysilane, fully stirred at 140 ° C for 7 hours, and then centrifuged for 30 minutes. 100 g of the lower layer product after centrifugation was taken and ground to 100 μm, and then treated with inorganic filler; then 100 g of ceramic fiber was added, and stirring was continued for 6 hours to obtain a slurry, which was sealed and stored in the dark.
[0035] The ablation-resistant coating prepared in this embodiment was coated with a thickness of 2 mm according to GB / T 17657-2022, and then subjected to a wear resistance test. The test results were as follows: 1. Ablation temperature 550℃; 2. Wear resistance at high temperature of 1400℃: wear value: 1.64g / 100r; 3. The mass loss rate after 500 rapid sample loadings at 1500℃ is less than 0.38%.
[0036] Comparative Example 4 The difference from Example 2 is that: The ablation-resistant coating is mixed with treated inorganic filler and ceramic fiber in a mass ratio of 1:1, and the preparation method is as follows: 56 g of expandable graphite, silicon carbide, zirconium carbide and ammonium polyphosphate powder in a mass ratio of 1:1:3:0.6 were mixed evenly, and then stirred with 80 g of γ-glycidyloxypropyltrimethoxysilane at 130°C for 12 h, and then centrifuged for 30 min. 100 g of the lower layer product after centrifugation was taken and ground to 100 μm to obtain a treated inorganic filler; then 100 g of ceramic fiber was added, and stirring was continued for 6 h to obtain a slurry, which was sealed and stored in the dark.
[0037] Performance Test: 1. Ablation temperature resistance 570 ℃; 2. Wear resistance at 1400℃: wear value: 1.61g / r; 3. The mass loss rate after 500 times of rapid sampling at 1500℃ is less than 0.41%.
[0038] Application Examples The slurry prepared in Examples 1 to 3 is coated on the inner wall of the ablation test sample delivery pipe made of metal or ceramic with a thickness of 2 mm to 6 mm, and the ablation-resistant coating is obtained after static curing, so that the pipe wall has ablation-resistant durability.
Claims
1. A method for preparing an ablation-resistant coating, characterized in that: The preparation steps are as follows: 1) Synthesis of P-Si with Si-O-Si cross-linked structure Tetramethoxysilane and γ-glycidyloxypropyltrimethoxysilane in a mass ratio of 1:(4-6) are added to tetrahydrofuran, wherein the material-liquid ratio is (50-70) g:200 mL; the temperature is raised to 80°C-100°C while stirring under nitrogen protection, and the stirring is stopped after the reaction is continued for 6h-10h; the polysilane filler P-Si with Si-O-Si crosslinking structure is obtained under nitrogen protection. The structural formula is as follows: 2) Treatment of inorganic fillers The expandable graphite, silicon carbide, zirconium carbide and ammonium polyphosphate raw material solid powders in a mass ratio of (1-1.1):(1-1.1):(3-3.2):(0.5-0.7) are uniformly mixed and added to tetramethoxysilane, wherein the material-liquid ratio is (55-57) g:(200-250) mL, and the mixture is fully stirred at a temperature of 140° C. to 150° C., and then centrifuged. The treated lower layer product is fully stirred with γ-glycidyloxypropyltrimethoxysilane at a temperature of 130° C. to 140° C., wherein the material-liquid ratio is 100 g:(200-250) mL, and then centrifuged again. The lower layer product after centrifugation is ground to obtain a treated inorganic filler; 3) Preparation of ablation-resistant coating At a temperature of 140°C to 150°C, the treated inorganic filler and P-Si having a Si-O-Si cross-linked structure are mixed and stirred for at least 10 hours, and then ceramic fibers are added and the mixing and stirring is continued for at least 5 hours to obtain the ablation-resistant coating, wherein the mass ratio of the treated inorganic filler, P-Si having a Si-O-Si cross-linked structure and ceramic fibers is (2-20):(1-9):(2-20).
2. The method for preparing an ablation-resistant coating according to claim 1, characterized in that: In step 2) the treatment of the inorganic filler, the particle sizes of the expandable graphite, silicon carbide, zirconium carbide and ammonium polyphosphate are 10 μm to 100 μm, and the mass ratio is 1:1:3:(0.5-0.7).
3. The method for preparing an ablation-resistant coating according to claim 1, characterized in that: In step 2) treating the inorganic filler, the particle size of the treated inorganic filler is 10 μm to 100 μm.
4. The method for preparing an ablation-resistant coating according to claim 1, characterized in that: In step 2) the treatment of the inorganic filler, the centrifugal treatment operation is performed for no less than 20 minutes.
5. The method for preparing an ablation-resistant coating according to claim 1, characterized in that: In step 3) the preparation of the ablation-resistant coating, the diameter of the ceramic fiber is 2 μm to 5 μm.
6. The ablation-resistant coating prepared by the method for preparing an ablation-resistant coating according to any one of claims 1 to 5, characterized in that: The composite material is a mixture of treated inorganic filler, P-Si having a Si-O-Si cross-linked structure and ceramic fiber in a mass ratio of (2-20):(1-9):(2-20).
7. An application of the ablation-resistant coating according to claim 6, characterized in that: The ablation-resistant coating is applied to the metal or ceramic tube wall and then allowed to stand and solidify to obtain the ablation-resistant coating.
8. The use of the ablation-resistant coating according to claim 7, characterized in that: The tube wall is the inner wall of the ablation test sample conveying tube.
9. The use of the ablation-resistant coating according to claim 7, characterized in that: The coating thickness of the ablation-resistant coating on the pipe wall is 2 mm to 6 mm.
Citation Information
Patent Citations
Hydrophobic and oleophobic coating as well as preparation method and application thereof
CN118126615A
Preparation of silicon carbide ceramics from the modification of an Si-H containing polysilane
US5204380A